PENGARUH PENDEKATAN RECIPROCAL TEACHING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SEMESTER GENAP SMP NEGERI 4 LIWA LAMPUNG BARAT - Buang Saryantono; Partono (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2019)
This study aims to determine the effect of the reciprocal teaching approach on student mathematics learning outcomes. This research uses an experimental method with two variables. The population in this study were all eighth grade students of SMP 4 Liwa West Lampung which consisted of 5 classes with a total of 122 students. Samples were taken 2 classes, namely class C as the experimental class which amounted to 22 and class VIII D as the control class consisting of 22 students. Sampling using Cluster Random Sampling technique. The research instrument used an essay test of 10 items which were first tested for validity and reliability. Simple statistical data analysis using the formula ttes. The results showed that thit = 2.60 from the distribution table at the level of 5% is known tdaf = 2.02. Proven thit> tafaf. Based on the results of the study, it can be concluded that there is an influence of the reciprocal teaching approach on the mathematics learning outcomes of class VIII Even Semester 4 SMPN 4 Liwa West Lampung Academic Year 2016/2017.